2021
DOI: 10.3389/fonc.2021.677776
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Lymphoma International Prognostic Index to Predict Venous Thromboembolic Events in Diffuse Large B-Cell Lymphoma Patients

Abstract: BackgroundVenous thromboembolic events (VTE) are commonly encountered in patients with lymphoma. Several risk assessments models (RAM) had attempted to identify higher risk patients with varying success. The International Prognostic Index (IPI) is a clinicopathological tool developed to help predict both response to treatment and prognosis of patients with diffuse large B-cell lymphoma (DLBCL).ObjectiveIn this study, we utilize the IPI index to identify group of patients with DLBCL at higher risk for VTE.Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…To the best of our knowledge, there are no published studies on using the NLR and PLR to assess the risk of VTE in patients with lymphoma. Intermediate/high risk score of IPI in patients with DLBCL was significantly more frequent in the patients who developed VTE, comparing to those without VTE, which is in line with the recently published data [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, there are no published studies on using the NLR and PLR to assess the risk of VTE in patients with lymphoma. Intermediate/high risk score of IPI in patients with DLBCL was significantly more frequent in the patients who developed VTE, comparing to those without VTE, which is in line with the recently published data [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…These meta-analyses, have also reported that the use of LMWH or VKA as primary thromboprophylactic agents were associated with a significant reduction in symptomatic VTE. Due to the inconvenience of daily injections with LMWH, difficulty in managing VKA in cancer patients, and the potential risk of bleeding complications among this high-risk patient population, these findings were never incorporated in routine clinical practice [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…33 In a very recent retrospective cohort study, comparing crude VTE rates in patients with advanced NSCLC ( n = 508), a higher risk was observed for ICI (23.5%) compared with chemotherapy (13.8%). 34 In contrast, a recent study reporting the cumulative risk of VTE in patients with advanced NSCLC undergoing systemic therapy ( n = 2,299) described a similarly high risk of VTE between patients treated with chemotherapy, ICI, and combined therapy of chemotherapy and ICI, with corresponding incidence rates of 13.5/100 PY, 18.0/100 PY, and 22.4/100 PY, respectively. 35 Further, in a recent health care database analysis including 1,823 patients with advanced cancers, a similarly high risk of VTE was observed with ICI therapy compared with patients treated with chemotherapy (6-month cumulative risk: 8.5 vs. 8.4%), with no significant differences in propensity score weighted analysis (weighted hazard ratio: 1.06; 95% CI: 0.88–1.26).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 91%